PENDIDIKAN HUMANIS PAULO FREIRE DALAM PEMBELAJARAN MATEMATIKA MI - Al Ayyubi, Ibnu Imam; Hayati, Ai Faridatul; Azizah, Elsa Nurul; Herdiansyah, Risman; Mirayanti, Ucu (Study Program of Madrasah Ibtidaiyah Teacher Education at Institut Agama Islam Pangeran Dharma Kusuma Indramayu, 2024)
This research aims at how humanist education proposed by Paulo Freire can be implemented in MI mathematics learning. This research uses a qualitative approach with a literature study method that refers to several sources of research data and data collection techniques in this research in the form of a study of Paulo Freire's perspective on humanistic education. The focus of the research that will be studied is Paulo Freire's humanist education in MI Mathematics learning. In this research, it can be concluded that mathematical abilities help individuals think logically, find solutions to problems, and make wise decisions. So that challenges and obstacles in the mathematics learning process at the MI level can be overcome by implementing a humanist learning approach, utilizing various interesting learning resources, and paying careful attention to each student. Thus, for further research, Paulo Freire's views can be implemented through MI Mathematics learning using a learning model that is relevant to students' conditions both in aspects of cognition and geography, furthermore, it can be linked based on gender and the level of students' initial mathematical abilities to see the differences and influences in the results. student learning.